The Determinants of Consumer Complaints - Oster, Sharon (The Review of Economics and Statistics, 1980)
While the rationale for conventional rate-of-return regulation has recently come into question, regulation designed to protect consumers by altering product quality has blossomed. In 1973, for example, eighteen major consumer bills were considered by Congress, among them requirements covering questions of product labelling, unit pricing, and truth in advertising. Currently there are 26 consumer offices scattered throughout the federal government, and over 200 city and state offices. In this paper, I try to explain variance in consumer complaints across different types of products. The tendency of consumers to complain about some products and not others is assumed to depend on some characteristics of both the industry producing that product and the people consuming it. The hypotheses generated are tested using data from the New Haven area. This paper is a first, exploratory study into the economic determinants of consumer complaints.